Analisis laporan arus kas untuk mengukur tingkat likuiditas pada PT. Sumber Jaya Adiperkasa Kota Tobelo tahun 2022-2024 - Tuatanassy, Sesillia; Sondakh, Jullie J.; Maradesa, Djeini (Manajemen Bisnis dan Keuangan Korporat, 2025)
The cash flow statement is one of the financial reports that presents the inflow and outflow of a company’s cash within a specific period. This study aims to determine the liquidity level of PT. Sumber Jaya Adiperkasa Tobelo for the period 2022–2024 based on the cash flow statement. The research method used is descriptive qualitative. The results show that the company’s cash flow experienced fluctuations. Operating cash flow decreased in 2022 but increased in 2024. Investment cash flow increased in 2022 but declined in 2024, while financing cash flow decreased and then rose again in 2024. The liquidity level, measured using the cash ratio, increased over the last three years with an average of 272%, indicating that the company’s financial condition is in good standing because the cash flow statement is able to cover the company’s short-term liabilities.